种冬小麦识别方法 (2019)
本发明公开了种冬小麦识别方法。利用冬小麦生育期内的遥感植被指数时序数据和物候历数据，通过分类类别设定、训练样本选取、样本时序曲线提取、冬小麦识别特征选择及参量化、最佳特征阈值确定和冬小麦识别模型构建，提取出区域范围内冬小麦的空间分布信息。本方法的特点是可基于未经去噪声处理的遥感植被指数时序数据进行冬小麦空间分布信息提取，具有较强的抗时序数据噪声能力；方法的稳定性和普适性较高，可应用于具有定物候差异的大范围区域的冬小麦分布信息遥感提取。 The invention discloses a method for identifying winter wheat. On the basis of remote-sensing vegetation index time sequence data and phonological calendar data during a growth period of winter wheat, classification type setting, training sample selection, sample time sequence curve extraction, winter wheat identification feature selection and parametrization, optimal feature threshold determination and winter wheat identification model construction are carried out successively to extract spatial distrubtion information of the winter wheat in a range. The method is characterized in that spatial distribution information extraction of the winter wheat can be carried out based on the remote-sensing vegetation index time sequence data without any de-noising processing, so that the anti-time sequen